TINDAK TUTUR EKSPRESIF MENGELUH DALAM ANIME ANI NI TSUKERU KUSURI WA NAI SEASON 4 - Dena Fath Malik (WIDAI Japanese Journal, 2023)
Speech acts refer to utterances expressed by speakers while performing an action and purpose with a specific meaning to elicit an expected response from the interlocutor. They can be categorized into various types according to the speaker's intention. Speech acts are divided into three types: locutionary, illocutionary, and perlocutionary. Within illocutionary acts, there are five types: assertive, directive, expressive, commissive, and declarative. Expressive speech acts can also be found in anime, along with various complaining strategies and other functions. The purpose of this research is to explore the functions of commissive speech acts and the complaining strategies used in a Japanese animated series titled "Ani ni Tsukeru Kusuri wa nai Season 4." The research methodology employed is descriptive qualitative using the observation method. The findings of this research revealed a total of 30 data instances. Commissive speech acts were represented by 12 instances, including 3 refusals, 3 promises, 5 offers, and 1 threat. Complaining strategies encompassed 18 instances, consisting of 1 indirect accusation, 8 expressions of annoyance, 4 descriptions of negative consequences, 1 gesture, 2 explicit blaming attitudes, 1 direct accusation, and 1 modified blaming attitude.